Fatal fried rice - Chien, Vivien (Chien, Vivien. Noodle shop mystery., 2021)
Lana Lee runs her family's Chinese restaurant in Cleveland's Asia Village like nobody's business. When it comes to actual cooking, however, she's known to be about a step up from boiling rice. So Lana decides to go to culinary school on the sly--and prove that she has what it takes in the kitchen after all. But when course instructor Margo Chan turns up dead after class, Lana suddenly finds herself on the case, frying pan in hand. Since she was the one who discovered the body, Lana must do double duty in finding the killer and clearing her name. Now, with or without the help of her boyfriend Detective Adam Trudeau, Lana launches her own investigation into Margo's life and mysterious death. Doing so leads her on a wild goose chase to and from the culinary school--and all the way back to the Ho-Lee noodle shop, where the guilty party may be closer than Lana thinks.